A Study in Vibration of a Large-Scale Hydraulic Cylinder Actuator via Numerical Simulation - Truong, Van-Thuan (Old Journal, 2018)
This paper presents a study in vibration field of a large-scale hydraulic cylinder actuator via numerical simulation. A model of hydrostatic hoisting machine which is built with dynamical parameters is executed for implementation and performance evaluation. The research has applied theories of vibration and fluid mechanics in calculation, analysis and modeling. Compressibility and viscous characteristics of hydraulic oil which have impacts on system dynamics are considered. Therefore, the mathematical model of this system is equivalent to a set of mass-spring-damper in investigation. The research results deduce a practically technical prediction in design and development of hydraulic systems using large-scale cylinders.